Impact of Voluntary Accreditation on Short‐Stay Rehabilitative Measures in U.S. Nursing Homes. Issue 4 (17th May 2013) - Wagner, Laura M.; McDonald, Shawna M.; Castle, Nicholas G.
Abstract Purpose To examine accreditation from nursing homes accredited by the Commission on Accreditation of Rehabilitation Facilities (CARF) and whether this is associated with improved rehabilitation care. Design Cross‐sectional association of CARF accreditation and quality. Methods Comparison of the short‐stay quality measures (influenza and pneumococcal vaccination; pain; delirium; pressures sores; five‐star quality and health inspection scores) between the sample of 246 CARF‐accredited homes compared with the 15, 393 nursing homes in the 2010 On‐Line Survey Certification of Automated Records (OSCAR). Findings CARF‐accredited nursing homes demonstrate better quality with regard to the short‐stay quality measures. Conclusions Approaches beyond traditional regulation and governmental inspections are necessary to improve the quality of care in nursing homes. Clinical Relevance During a patient's rehabilitation stay, minimizing iatrogenic complications is paramount. Given the findings of this study, it is unfortunate that very few nursing homes are CARF accredited.